Proposed Improvements to Production Facility Layout Using ARC and ARD at Home Industry Aurora Official - Muhammad Hasbi Ash Shiddiqi; Elly Ismiyah; Yanuar Pandu Negoro (G-Tech: Jurnal Teknologi Terapan, 2025)
Home Industry Aurora Official, which is engaged in the manufacture of pillows and baby mattresses, faces problems related to inefficient facility layouts in the workflow. Suboptimal layouts result in excessive waste of distance, which affects production time and reduces operational efficiency. This study aims to design a more efficient facility layout by minimizing the distance between production processes. The methods used in this study are the ARC (Activity Relationship Chart) and ARD (Activity Relationship Diagram) methods, which can help design layouts based on the relationships between production activities and determine the relationships between activities based on their priority level of proximity. Based on the analysis results, the initial layout produces a total distance of 940 meters, while the two alternative proposed layouts produce distances of 310 meters and 405 meters respectively. Of the two proposed layouts, proposed layout 1 was chosen as the proposed layout for the company with a total distance of 310 meters, with a decrease of 67% from 100% of the total distance of the initial layout. The results of this study indicate that the application of proposed layout 1 can improve workflow efficiency and reduce waste time in the production process.